Inflammation time-axis in aseptic loosening of total knee arthroplasty: A preliminary study - Dyskova, Tereza; Kriegova, Eva; Slobodova, Zuzana; Zehnalova, Sarka; Kudelka, Milos; Schneiderova, Petra; Fillerova, Regina; Gallo, Jiri (PloS one, 2019)
OBJECTIVE: Aseptic loosening (AL) is the most frequent long-term reason for revision of total knee arthroplasty (TKA) affecting about 15-20% patients within 20 years after the surgery. Although there is a solid body of evidence about the crucial role of inflammation in the AL pathogenesis, scared information on inflammation signature and its time-axis in tissues around TKA exists. DESIGN: The inflammation protein signatures in pseudosynovial tissues collected at revision surgery from patients with AL (AL, n = 12) and those with no clinical/radiographic signs of AL (non-AL, n = 9) were investigated by Proximity Extension Assay (PEA)-Immunoassay and immunohistochemistry. RESULTS: AL tissues had elevated levels of TNF-family members sTNFR2, TNFSF14, sFasL, sBAFF, cytokines/chemokines IL8, CCL2, IL1RA/IL36, sIL6R, and growth factors sAREG, CSF1, comparing to non-AL. High interindividual variability in protein levels was evident particularly in non-AL. Levels of sTNFR2, sBAFF, IL8, sIL6R, and MPO discriminated between AL and non-AL and were associated with the time from index surgery, suggesting the cumulative character of inflammatory osteolytic response to prosthetic byproducts. The source of elevated inflammatory molecules was macrophages and multinucleated osteoclast-like cells in AL and histiocytes and osteoclast-like cells in non-AL tissues, respectively. All proteins were present in higher levels in osteoclast-like cells than in macrophages. CONCLUSIONS: Our study revealed a differential inflammation signature between AL and non-AL stages of TKA. It also highlighted the unique patient's response to TKA in non-AL stages. Further confirmation of our preliminary results on a larger cohort is needed. Analysis of the time-axis of processes ongoing around TKA implantation may help to understand the mechanisms driving periprosthetic bone resorption needed for diagnostic/preventative strategies.
Keywords: senioři; Histiocytes; Inflammation; senioři nad 80 let; reoperace; cytokiny; zánět; totální endoprotéza kolene; Middle Aged; mužské pohlaví; Cytokines; selhání protézy; Reoperation; Arthroplasty, Replacement, Knee; resorpce kosti; histiocyty; Aged, 80 and over; Bone Resorption; Macrophages; ženské pohlaví; Humans; Osteoclasts; osteoklasty; lidé středního věku; makrofágy; Female; Aged; Prosthesis Failure; lidé; Male